Interactive effect of negative affectivity and anxiety sensitivity in terms of mental health among Latinos in primary care. (30th September 2016) - Zvolensky, Michael J.; Paulus, Daniel J.; Bakhshaie, Jafar; Garza, Monica; Ochoa-Perez, Melissa; Medvedeva, Angela; Bogiaizian, Daniel; Robles, Zuzuky; Manning, Kara; Schmidt, Norman B.
Abstract: From a public health perspective, primary care medical settings represent a strategic location to address mental health disapirty among Latinos. Yet, there is little empirical work that addresses affective vulnerability processes for mental health problems in such settings. To help address this gap in knowledge, the present investigation examined an interactive model of negative affectivity (tendency to experience negative mood states) and anxiety sensitivity (fear of the negative consequences of aversive sensations) among a Latino sample in primary care in terms of a relatively wide range of anxiety/depression indices. Participants included 390 Latino adults ( M age =38.7, SD =11.3; 86.9% female; 95.6% reported Spanish as first language) from a primary care health clinic. Primary dependent measures included depressive, suicidal, social anxiety, and anxious arousal symptoms, number of mood and anxiety disorders, and disability. Consistent with prediction, the interaction between negative affectivity and anxiety sensitivity was significantly related to suicidal, social anxiety, and anxious arousal symptoms, as well as number of mood/anxiety diagnoses and disability among the primary care Latino sample. The form of the interactions indicated a synergistic effect, such that the greatest levels of each outcome were found among those with high negative affectivity and high anxiety sensitivity. There was a trending interaction for depressive symptoms. Overall, these data provide novel empirical evidence suggesting that there is a clinically-relevant interplay between anxiety sensitivity and negative affectivity in regard to the expression of anxiety and depressive symptoms among a Latino primary care sample. Highlights: We examined anxiety sensitivity and negative affect and psychopathology among Latinos. Anxiety sensitivity and negative affect interaction related to suicide. Anxiety sensitivity and negative affect interaction related to social anxiety. Anxiety sensitivity and negative affect interaction related to anxious arousal.